Associations between physical frailty and living arrangements in Japanese older adults living in a rural remote island: The Shimane CoHRE study - Ryo Miyazaki; Takafumi Abe; Shozo Yano; Kenta Okuyama; Naoki Sakane; Hitoshi Ando; Minoru Isomura; Masayuki Yamasaki; Toru Nabika (Journal of General and Family Medicine, 2022)
Abstract Background Living arrangements have been known to be associated with physical frailty. However, the prevalence of frailty and its risk factors in remote islands is not understood. We examined the association between living arrangements and objectively measured frailty among older adults living in a remote island of Japan. Methods Among older people living in Okinoshima, 656 older adults (75.6 ± 6.4 years) were analyzed. Physical frailty (robust, prefrailty, or frailty) was assessed using the 5‐item frailty phenotype (unintentional weight loss, self‐reported exhaustion, weakness, slow walking speed, and low physical activity). Physical functions (muscle mass, gait speed, and grip strength) were measured objectively. Results The prevalence of frailty and prefrailty was 6.6% and 43.8%, respectively. Living with a spouse resulted in a significantly lower prevalence of frailty (p < 0.001) compared with other living arrangements. All objectively measured physical functions among those who lived with a spouse were significantly superior to those who lived with family or alone (p < 0.001). Multinomial logistic regression showed that living alone was significantly associated with frailty (odds ratio [OR] 2.36, 95% confidence interval [CI] 1.07–5.24) and prefrailty (OR 1.75, 95% CI 1.14–2.69) after adjusting for all covariates. Conclusion The prevalence of frailty on remote islands seemed similar to that in urban areas. Older people living in remote islands might be able to maintain their physical health. Furthermore, living alone may correlate with increased risks of frailty and prefrailty. Among elderly individuals on remote islands, living with a spouse might be desirable to prevent (pre)frailty.